2010
DOI: 10.1016/j.ydbio.2009.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Pdlim7 (LMP4) regulation of Tbx5 specifies zebrafish heart atrio-ventricular boundary and valve formation

Abstract: Tbx5 is involved in congenital heart disease, however, the mechanisms leading to organ malformation are greatly unknown. We hypothesized a model by which the Tbx5 binding protein Pdlim7 controls nuclear/cytoplasmic shuttling and function of the transcription factor. Using the zebrafish, we present in vivo significance for an essential role of Tbx5/Pdlim7 protein interaction in the regulation of cardiac formation. Knock-down of Pdlim7 results in a non-looped heart, strikingly reminiscent of the tbx5 heartstring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
78
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(84 citation statements)
references
References 77 publications
(129 reference statements)
6
78
0
Order By: Relevance
“…The expanded AVC phenotype of wkm mutants is phenotypically indistinguishable from the defect seen in zebrafish tbx5, apc and hey2 mutants. In these cases, an expansion of bmp4 expression throughout the ventricular myocardium is observed and is associated with EC marker expansion (Camarata et al, 2010;Garrity et al, 2002;Hurlstone et al, 2003;Rutenberg et al, 2006). Here, we show that, downstream of tmem2, ectopic bmp4 expression is functionally responsible for the expansion of the immature AVC.…”
Section: Avc Expansion In Wkm Mutants Is Driven By Bmp4supporting
confidence: 49%
See 1 more Smart Citation
“…The expanded AVC phenotype of wkm mutants is phenotypically indistinguishable from the defect seen in zebrafish tbx5, apc and hey2 mutants. In these cases, an expansion of bmp4 expression throughout the ventricular myocardium is observed and is associated with EC marker expansion (Camarata et al, 2010;Garrity et al, 2002;Hurlstone et al, 2003;Rutenberg et al, 2006). Here, we show that, downstream of tmem2, ectopic bmp4 expression is functionally responsible for the expansion of the immature AVC.…”
Section: Avc Expansion In Wkm Mutants Is Driven By Bmp4supporting
confidence: 49%
“…Mutants for genes such as ugdh (jekyll) (Walsh and Stainier, 2001), notch1 (Timmerman et al, 2004) and foxn4 (slipjig) (Chi et al, 2008) exhibit a loss or diminution of EC development. By contrast, mutations in apc (Hurlstone et al, 2003), tbx5 (heartstrings) (Camarata et al, 2010;Garrity et al, 2002) or hey2 (gridlock) (Rutenberg et al, 2006) result in an expansion of the AVC. In this latter category of mutants, the AVC-chamber boundary is compromised.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, mutations that affect atrial and ventricular development have been reported [10,11,12]. Embryonic and postembryonic cardiac development [13,14] and adult zebrafish electrocardiogram (ECG) [15] have been described.…”
Section: Introductionmentioning
confidence: 99%
“…This protein synergistically acts with Tbx20, BMP4, GATA4, Nkx2-5 and other factors to regulate the expression of many chamber-specific genes 8,14,20 . It also restricts the expression of Tbx2 (tbx2b in zebrafish) and has2 (hyaluronan synthase 2) at the AVC to facilitate the formation of the endocardial cushion and valve 21 .…”
mentioning
confidence: 99%